Towards a Better Use of Antimicrobials on Farms: Insights from a Participatory Approach in the French Pig and Poultry Sectors - Christian Ducrot; Marie-Jeanne Guénin; Anne Hemonic; Nathalie Rousset; Yannick Carre; Charles Facon; Philippe Le Coz; Jocelyn Marguerie; Jean-Marc Petiot; Maxime Jarnoux; Mily Leblanc-Maridor; Mathilde Paul; et al. (MDPI AG, 2022)
Despite the strong decrease in antimicrobial use in the French poultry and pig sectors over the last decade, room for improvement remains. A participatory approach was set up in France, involving representatives of veterinarians, the pig and poultry industries, technical institutes, the French Ministry of Agriculture, and researchers, to further improve how antimicrobials are used on farms. By successively defining a shared, long-term vision of future antimicrobial use on farms, identifying lock-in mechanisms impeding this future vision from being realized, and articulating practical questions on how to move in the desired direction, the group rapidly reached a consensus. The results highlight the need for consensual standardized monitoring tools that would allow farmers and veterinarians to jointly monitor the health, welfare, antimicrobial resistance, and antimicrobial use on farms. Other results relate to better communication and training for citizens regarding animal health, animal welfare, and proper antimicrobial use; some benefits but also counterproductive effects of antibiotic-free labels that imperil animal health and welfare; the economic competitiveness of farms on international markets; and the economic sustainability of farm animal veterinary practices. These results call for a concerted way to produce tools for farmers and veterinarians and the broader involvement of other food sector actors.